Chart showing the track of H. M. Sledge Resolute, in charge of Mr. A. R. Bradford, Surgeon, detached under the orders of Lieut: F. L. McClintock / Day & Son Lithrs. to the Queen - Bradford, A. R. (Hydrographic Office of the Admiralty, 1852)
"To face page 203" -- upper right margin. Shows outward and homeward tracks. Color;